2002
DOI: 10.1007/s00296-002-0185-z
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss and middle ear involvement in rheumatoid arthritis

Abstract: In this controlled study, hearing and middle ear functions were investigated in 37 patients with rheumatoid arthritis (RA) and 35 controls in order to study the prevalence and the nature of hearing loss in RA. The prevalence of the hearing impairment was significantly higher in the RA group, and the majority was bilateral (P<0.001). Of the patients, 35.1% had sensorineural (SN), 24.3% had conductive loss, and 10.8% had a mixed type of hearing loss. The hearing loss was positively correlated to the Steinbrocker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
5
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 5 publications
4
47
5
11
Order By: Relevance
“…Çeşitli çalışmalarda işitme kaybının 0 -%17,4 arasında iletim tipi işitme kaybı [10,13,15] olduğu, 0 -%48 arasında ise SN tipte işitme kaybı [13,18] olduğu rapor edilmiştir. Bu hasta grubunda SN işitme kaybının patofizyolojisi tam olarak bilinmemekle beraber nörit, vaskülit ve ototoksik ilaç kullanımı gibi çeşitli sebepler suçlanmıştır [8]. Hughes ve ark.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Çeşitli çalışmalarda işitme kaybının 0 -%17,4 arasında iletim tipi işitme kaybı [10,13,15] olduğu, 0 -%48 arasında ise SN tipte işitme kaybı [13,18] olduğu rapor edilmiştir. Bu hasta grubunda SN işitme kaybının patofizyolojisi tam olarak bilinmemekle beraber nörit, vaskülit ve ototoksik ilaç kullanımı gibi çeşitli sebepler suçlanmıştır [8]. Hughes ve ark.…”
Section: Discussionunclassified
“…Ancak RA da işitme sistemi tutulumunun patofizyolojisi ve işitme kaybının tipi konusunda yazarlar arasında görüş ayrılıkları vardır. Bu hastalarda; iletim tipi, sensorinö-ral (SN) tip veya her ikisini de içeren işitme kayıpları rapor edilmiş olmakla birlikte, en sık (%25-72 oranın-da) sensorinöral tip işitme kaybının olduğu bildirilmiştir [3,[6][7][8][9]. RA'da iç kulak tutulumunun varlığı tam olarak anlaşılamamış olmasına rağmen, nörit, vaskülit veya ilaç ototoksisitesine bağlı olarak tutulabileceği belirtilmiştir [10][11][12].…”
unclassified
“…SNİK'in daha sık olduğu ( %24-60) ve RA'nın iç kulağı etkilemesi ile meydana geldiği rapor edilmiştir. 5,6 Aynı zamanda iletim tipi işitme kaybı da rapor edilmiş; fakat daha düşük oranda (%0-13) olduğu gözlenmiştir. 3,6,7 RA, arterit ve nö-ropatiyle 8 , otoimmun mekanizmayla veya tedavisinde kullanılan bazı ilaçların toksik etkisiyle de işitme bozukluğuna sebep olabilir.…”
Section: Introductionunclassified
“…133 Small conductive and sensorineural hearing losses have been reported in a proportion of patients with rheumatoid arthritis. 132,[136][137][138] It has been suggested that the sensorineural hearing impairment may be due to an increase in compressive force on the labyrinth, 131 perhaps due to a relative inability to buffer static pressure changes. However, alternative hypotheses include the effects of systemic neuritis, vasculitis or salicylate toxicity.…”
Section: Flexibility and Pressure-bufferingmentioning
confidence: 99%